Effects of Conformal Radiotherapy on Thyroid and Parathyroid Functions in Head-and-neck Carcinoma: A Single-institutional, Prospective, and Observational Study - Rupasree Pal; Debottam Barman; Bodhisattwa Dutta; Bithi Pal; Snigdha Hazra; Asit Ranjan Deb (Journal of Radiation and Cancer Research)
Introduction: Assessment of acute and late effects of conformal radiotherapy on thyroid and parathyroid functions along with the evaluation of Dosimetric correlation with radiation-induced hypothyroidism (RIH) was the purpose of this study. Subjects and Methods: In this study, thyroid and parathyroid functions were obtained from 40 patients of head-and neck carcinoma who had received conformal radiotherapy, at baseline, 6 weeks and 6 months after radiotherapy. The mean radiation dose (Dmean), volume, V20, V30 and V50 of thyroid gland were analyzed for Dosimetric correlation with RIH. Statistical Analysis: IBM SPSS software version 23 was used for the statistical analysis. Descriptive statistics, independent sample t-test, and pair sample t-test were performed. Results: The median follow-up period was 29 months. During the follow-up, 40% of total patients had developed RIH, among whom 37.5% of patients had laryngeal carcinoma as primary site. Dmean and volume of thyroid gland were found to be the strong predictors for RIH with P < 0.01. Fall in parathyroid hormone level after 6 weeks and 6 months of radiotherapy was also significant. Conclusion: Conformal radiotherapy has substantial effect on thyroid and parathyroid functions. Dmean and volume of thyroid gland can be considered as useful risk assessment tools for RIH.